Optical ceramics and crystals in laser and optical applications - Ling, Hsih Hwa (2018)
Ceramics are both the oldest materials made by human and also the most sophisticated today. The development and application of a ceramics is highly dependence on its’ properties. The objective of this project is to provide an explanation on how advanced ceramics and crystals are applicable in laser and optical applications by analyzing the arrangement of atoms and grain boundaries, which ultimately characterized the electrical properties. Semiconductor devices are highly involved in the electronics industries. Through the understanding the relationship between of light and ceramics, such as optical fibre, it can be seen the applications of advanced ceramics have benefited the communication and healthcare industry in many areas.